CFD for wastewater treatment an overview - Samstag, R W (Water science and technology : a journal of the International Association on Water Pollution Research, 2016)
Computational fluid dynamics (CFD) is a rapidly emerging field in wastewater treatment (WWT), with application to almost all unit processes. This paper provides an overview of CFD applied to a wide range of unit processes in water and WWT from hydraulic elements like flow splitting to physical, chemical and biological processes like suspended growth nutrient removal and anaerobic digestion. The paper's focus is on articulating the state of practice and research and development needs. The level of CFD's capability varies between different process units, with a high frequency of application in the areas of final sedimentation, activated sludge basin modelling and disinfection, and greater needs in primary sedimentation and anaerobic digestion. While approaches are comprehensive, generally capable of incorporating non-Newtonian fluids, multiphase systems and biokinetics, they are not broad, and further work should be done to address the diversity of process designs. Many units have not been addressed to date. Further needs are identified throughout, but common requirements include improved particle aggregation and breakup (flocculation), and improved coupling of biology and hydraulics